MOBILITY OF RHENIUM, PLATINUM GROUP ELEMENTS AND ORGANIC CARBON DURING BLACK SHALE WEATHERING - Jaffe L.A.; Peucker-Ehrenbrink B.; Petsch S.T. (My University, 2002)
This study investigates the effects of black shale weathering on the Re-Os isotope system, platinum group element concentrations and the degradation of organic matter. Samples from a weathering profile in Late Devonian (~365 Myr) Ohio Shale show a pronounced decrease (~77%) in organic carbon (Corg) near the present soil surface, relative to the interior portion of the outcrop. A similar trend is observed for total N (~67% loss). Conversely, organic phosphorus (Porg) concentrations increase by ~59% near the soil surface. The decrease in Corg is accompanied by a pronounced decrease in Re (~99%) and, to a lesser extent, Os (~39%). Palladium and Pt do not appear to be significantly mobile. The effects of Re and Os mobility on the Re-Os isotope system are significant: none of the samples plots on a 365 Myr isochron. Rather, the samples define a trend with a slope corresponding to an age of ~18 Myr with an initial 187Os/188Os of ~6.1. This indicates recent disturbance of the Re-Os system. Isotope mass balance calculations imply that the labile fraction of Os is significantly more radiogenic (187Os/188Os of ~7.8) than the average of the unweathered samples (187Os/188Os of ~6.4). Based on data from this study, the molar ratio of labile Re to Corg in Ohio Shale is estimated at 7x10-8. We estimate the present-day riverine, black shale-derived Re flux to seawater using literature data on Re burial in anoxic marine sediments, and assuming steady-state between Re release during black shale weathering and Re burial in anoxic marine sediments. Then, the labile Re/Corg observed in this study implies that ~0.5 Tmol of Corg is released annually from weathering of black shales, a trace lithology in the continental crust. This flux corresponds to ~12% of the estimated annual CO2 flux from oxidative weathering of sedimentary rocks. The labile molar Re/Os of ~270 indicates that black shale weathering releases ~130 mol Os per year, which accounts for ~7% of the riverine Os input to seawater. The data from this study support the notion that the crustal cycles of labile Corg, Re and Os are tightly coupled. Gray shales, which are less Corg-, Re- and Os-rich, but much more abundant in the continental crust than black shales, are likely to be even more important continental sources of Re and Os to seawater.
Keywords: BLACK SHALE; WEATHERING; OSMIUM; RHENIUM; ORGANIC CARBON; GEOCHEMICAL CYCLE; Devonian; Paleozoic::Devonian; Палеозой::Девонская